The extent of the legality of marriage with the intention of divorce in the light of Quran and Sunnah - Ibrahim, Nouri Abdel Rahman; Haidar, Mustafa Mohamed Amin (Journal of Islamic Sciences, 2019)
It is one of the contemporary jurisprudential issues and issues in which there is a great deal of controversy between the analyst and the mahram. It is the marriage with the intention of divorce, so the scholars say that between permissibility and prohibition, I have tried hard to prove what is in accordance with the law of Allah and the Sunnah of His Prophet Muhammad, peace and blessings be upon him , And then the words and deeds of the Companions in this particular question; because it carries a great danger, and a door of doors that escape the man of the responsibilities of marriage and exploited the subject Muslims who travel to the country of alienation, whether to study or trade, or tourism, and fear falling into Fornication shall be taken from the mouth The dissolution of the marriage with the intention of divorce without regard to the consequences and consequences On that. The Prophet (peace and blessings of Allaah be upon him) said: "No one believes in you until he loves you. " The Prophet (peace and blessings of Allaah be upon him) said: "No one believes in you until he loves you. For his brother what he loves for himself)) In this research was discussed this issue and the views of scientists and discuss the opinion of Majizin and Mnainin individually in detail and then was weighted not permissible such a marriage and the statement of psychological damage to the wife and social damage.